Performance of hybrid mass damper system applied to a 36 storey high rise building. - Nagashima, Ichiro (Earthquake engineering & structural dynamics.)
A recently developed hybrid mass damper (HMD) system and its application to a 36 storey high rise building with a bi-axial eccentricity, located in Tokyo, are presented. This new HMD system utilizes a gear type pendulum and a linear actuator. Here, the gear type pendulum is employed to make the natural period of the auxiliary mass comparatively long while minimizing the height of the device and the linear actuator, on the other hand, ensures smooth and noiseless operation of the system. There are several special features in the control method as well; two HMD systems are applied to control the transverse torsional coupled vibration of the building, and also variable gain feedback (VGF) control technique has been developed to fully utilize the capacity of the HMD system from weaker to stronger external excitations. Free vibration tests as well as control of wind vibrations of the building induced by the Typhoon 9810 in 1998 were used to verify the performance of the control system. It was found that the maximum and the root mean square acceleration responses of the building were reduced to 63 percent and 47 percent of the corresponding uncontrolled accelerations. Finally, the control performance of the system was confirmed.